Reception and Circulation of Carl Rogers’s Humanistic Psychology in Brazil - Castelo Branco, Paulo Coelho; Dias Cirino, Sérgio (Revista de Psicología, 2017)
According a historiographical perspective, we aimed to (re)organize, revisit and reflect the reception and circulation of Carl Rogers’ humanistic psychology in Brazil. Initially, we present the reception and circulation concepts and their implications for the history of psychology in context. Posteriorly, we revised four historical moments of reception and circulation of Rogerian ideas in Brazil, namely, prehistory (1945-1976), fertilization (1977-1986), decline (1987-1989) and ascension / rebirth (1990 upward). Then, we analyze the translations of Rogers’ works to the Brazilian Portuguese, specifying how they collaborated for this reception and circulation in the 1970s-2010s. We reflect that, currently, in Brazil, there just a few Rogers’ books in edition and there are some methodological, autobiographical and clinical works that have not been translated. There is a difficulty in the total access of Rogers’ research plans and theoretical, clinical and educational foundation, as well as the partial knowledge of the author’s life and work according to his narratives. We argue, finally, that these factors contributed for the person-centered approach development with local specificities, mainly, phenomenological and existential.